From disaster response to prevention : companion paper to the Disaster Risk Management Policy - Keipi, Kari (IDB WashingtonUS, 2007)
Provides the background and context of the new policy. Underscores the need for reducing vulnerability in Latin American and the Caribbean. Establishes the merits of a shift to proactive disaster risk management embodied in the policy.